Avβ3 integrin: Pathogenetic role in osteotropic tumors. Issue 1 (October 2015) - Stucci, Stefania; Tucci, Marco; Passarelli, Anna; Silvestris, Franco
Abstract The interplay of cancer cells and accessory cells within the microenvironment drives signals regulating the proliferation, migration and skeleton colonization. Osteotropism of tumor cells depends on chemokine activation, production of soluble factors and defective gene expression that cooperate within the metastatic niche to the bone resorbing functions of osteoclasts. Adhesion of cancer cells to the extracellular matrix is regulated by integrins as αvβ3 that enhances their invasiveness, pro-tumor angiogenesis and skeleton invasion. Therefore, αvβ3 signaling is implicated in enhancing osteotropism of breast and prostate cancers as well as of multiple myeloma. Targeting of αvβ3 has been adopted to restrain the tumor progression in several cancer models leading to improvement of overall survival as effect of the reduction of both tumor burden and osteotropism by malignant cells. Here, we review both the role of αvβ3 in malignant osteoclastogenesis and its potential targeting to restrain the bone colonization by skeleton invading cancers.